A portable borehole temperature logging system using the four-wire resistance method - AKKOYUNLU, BÜLENT OKTAY; ERKAN, KAMİL; TAYANÇ, METE (IOP PUBLISHING LTD, 2017)
High-quality temperature-depth information from boreholes with a depth of 100 m or more is used in geothermal studies and in studies of climate change. Electrical wireline tools with thermistor sensors are capable of measuring borehole temperatures with millikelvin resolution. The use of a surface readout mode allows analysis of the thermally conductive state of a borehole, which is especially important for climatic and regional heat flow studies. In this study we describe the design of a portable temperature logging tool that uses the four-wire resistance measurement method. The four-wire method enables the elimination of cable resistance effects, thus allowing millikelvin resolution of temperature data at depth. A preliminary two-wire model of the system is also described. The portability of the tool enables one to collect data from boreholes down to 300 m, even in locations with limited accessibility.
Keywords: borehole temperature logging; geothermal gradient; four-wire method